Self-assessment: An Iterative And Continuous Process. The Case Of First Year Master Computer Science Students At Dr Moulay Tahar University-saida, Algeria - Kherraz, Mokhtaria (جامعة الوادي - University of Eloued, 2023)
Self-assessment which has at last grounded itself as an effective strategy in EFL teaching/learning context requires more attention and care. In this vein, the present paper attempts to highlight assessment as a general issue then specifies to self-assessment as a specific concern. For data collection tools, two instruments have been used: a questionnaire was addressed to first year master students in the Computer Science department at Dr Moulay Tahar university-Saida and a semi-structured interview was conducted with three English teachers from different departments. The gathered data has been analysed using both quantitative and qualitative approaches. The results revealed that though self-assessment is adopted as a strategy in teaching, teachers need training to be able to implement self-assessment effectively
articl
Keywords: self-assessment ; effective strategy ; master students